ESD-SDGs in Teaching among Geography Teachers - Mohd Zaki, Said; Nor Asniza, Ishak; Mohammad Zohir, Ahmad @ Shaari (GEOGRAFI, 2024)
Education for Sustainable Development (ESD) is an important agenda in schools towards the  Sustainable Development Goals (SDGs) and to achieve UNESCO's 2030 Agenda. Both conceptual frameworks, ESD-SDGs are implemented in pedagogic activities and important to the achievement of the SDGs. The purpose of this study is to measure ESD-SDG concept in teaching, among Geography teachers. A quantitative study was conducted involving 252 samples from 350 Geography teachers in Penang through a survey method. The findings based on mean score showed as “often”carried out  by Geography teachers in term of “experiential-learning (active) approach” (M=3.95, SD=0.809), “real-world learning approach” (M=3.40, SD=1.065)  and “critical-problem solving learning approach” (M=3.53, SD=1.011). Geography teachers implemented the “experiential-learning (active) approach” in teaching  by “Emphasis on sustainable living”, “Cultivate the value of appreciating all life and nature” and “Spread the ideals of harmony, peace, and respect for one another". Furthermore, teachers choose “sometime” in implementing the global citizenship project based on the “Real-world learning approach”. As a worldwide need to teach and promote students about sustainable development (SD) in line with SDG4.7, the findings of the study show that the pedagogical approach to sustainable development towards the implementation of the ESD-SDGs concept is insufficient and needs to be improved especially students-centered learning (SCL) in the teaching approach.